2016
DOI: 10.1002/2016gl069284
|View full text |Cite
|
Sign up to set email alerts
|

Were the May 2012 Emilia‐Romagna earthquakes induced? A coupled flow‐geomechanics modeling assessment

Abstract: Seismicity induced by fluid injection and withdrawal has emerged as a central element of the scientific discussion around subsurface technologies that tap into water and energy resources. Here we present the application of coupled flow‐geomechanics simulation technology to the post mortem analysis of a sequence of damaging earthquakes (Mw = 6.0 and 5.8) in May 2012 near the Cavone oil field, in northern Italy. This sequence raised the question of whether these earthquakes might have been triggered by activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 27 publications
6
59
0
Order By: Relevance
“…Lastly, our structural model could be used as reference to perform a geologically realistic 3D geomechanical modeling of the stress changes resulting from the combined effects of wastewater injection and hydrocarbon withdrawal from the reservoir. Such a modeling would enable to model the observed induced seismicity and to quantitatively assess the likelihood to trigger earthquakes on optimally oriented faults evidenced in our study34. At a more general scale, our results reinforce the need of a multidisciplinary approach combining advanced seismological analysis with reliable structural models of hydrocarbon reservoirs for a thorough understanding of induced seismicity.…”
Section: Discussionsupporting
confidence: 70%
“…Lastly, our structural model could be used as reference to perform a geologically realistic 3D geomechanical modeling of the stress changes resulting from the combined effects of wastewater injection and hydrocarbon withdrawal from the reservoir. Such a modeling would enable to model the observed induced seismicity and to quantitatively assess the likelihood to trigger earthquakes on optimally oriented faults evidenced in our study34. At a more general scale, our results reinforce the need of a multidisciplinary approach combining advanced seismological analysis with reliable structural models of hydrocarbon reservoirs for a thorough understanding of induced seismicity.…”
Section: Discussionsupporting
confidence: 70%
“…In all scenarios, the pressure drop in the producing reservoir compartment was significantly stronger than the pressure drop in the fault zone (i.e., at the rupture point). Hence, we conclude that the assumption of similar pressure drops in the fault and adjacent reservoirs, as suggested in previous studies [e.g., Mulders , ; Orlic et al ., ; van den Bogert , ; Wassing et al ., ; Orlic , ; Juanes et al ., ], is a poor approximation of several physical processes. The deviation of the magnitudes in the different scenarios can be explained by different shear stress accumulation during production, different pore pressure distribution in the fault (i.e., fault strength), and different caprock rheology.…”
Section: Discussionmentioning
confidence: 99%
“…The two strongest events of the sequence caused structural and nonstructural damage to residential, industrial, and public buildings as well as 27 fatalities [ Masi et al , ]. The 20 May earthquake occurred on the western segment of the Middle Ferrara fault, while the 29 May earthquake nucleated about 10 km to the southwest of the 20 May event epicenter and occurred on the Mirandola fault, which bounds the Cavone oil field from the north [ Juanes et al , ] (see Figure ). The proximity of the sequence to this industrial site encouraged speculation on the possibility that earthquakes have been affected by anthropogenic factors.…”
Section: The Problem Of Fluid‐induced Seismicity In Europementioning
confidence: 99%
“…These results have raised political discussions and strong debates in Italy and worldwide [ Cartlidge , ]. On April 2014 the company managing the exploitation of the Cavone field funded a research activity to be carried out by another group of experts, which demonstrated that there was no physical reason to suspect that pressure changes associated to the exploitation of the Cavone oil field triggered the earthquakes that occurred in the Emilia Romagna region in 2012 [ Astiz et al , ; Juanes et al , ]. Furthermore, a quantitative probabilistic approach proposed by Dahm et al [] to discriminate induced, triggered, and natural earthquakes was applied to this seismic sequence.…”
Section: The Problem Of Fluid‐induced Seismicity In Europementioning
confidence: 99%
See 1 more Smart Citation